Study of Cymbopogon citratus (lemongrass) essential oil extraction technique - Norashazrin, Yusof (2010)
The Lernongrass (Cymbopogon Citratus) essential oil was a significant interest as a new high-value essential oil especially in pharmaceutical, aromatherapy aid and cosmetics industries which give large opportunities for global marketing. This study obtained to identify the effect of the retention time and particle size on production of Lernongrass essential oil by using Soxhiet extraction method. Soxhiet extraction method used to obtain essential oil processes are not expensive but can induce thermal degradation, hydrolysis and water solubilization of some fragrance constituents. Ratio of Lemongrass and ethanol use was 1:3 were placed in the Soxlet extraction setup. The essential oil components were identified by using GC-MS. The result shows stem can obtained higher yield at highest retention time and lowest particle size. The dominated compound from leaves, stern and mixture was Citral (1.27%, 0.86% and 2.74%) follow by Geraniol (0.58%, 0.61% and 0.88%) an oxygenated compound for effect of particle size. The compound from effect of retention time for leaves, stem and mixture is Neral (33.95%, 2.11% and 3.17%) followed by Geranial (40.64%, 3.98% and 2.98%). As a conclusion stem obtained greater yield with longest time and lowest particle size and also high percentage of oxygenated compounds compare with leaves and mixture. Furthermore stem shows a good alternative part of Lemongrass to produce essential oil.